2018
DOI: 10.1016/j.jpain.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Patient Weight on Pain-Related Judgements About Male and Female Chronic Low Back Pain Patients

Abstract: Compared to men, women report more pain and are at increased risk for having pain discounted or misattributed to psychological causes. Overweight individuals experience high rates of pain and may receive suboptimal care due to provider bias. Research suggests the social consequences of being overweight are worse for women than men, and that gender and weight uniquely and interactively impact pain experience and care. Healthy participants (N=616) viewed six videos of back pain patients (1 female and 1 male of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
2
17
0
1
Order By: Relevance
“…Women with chronic pain report greater hostility and dismissal 45 and are more likely to have their pain attributed to psychological issues. 46 These disparities appear to be reinforced through gender stereotypes that attribute distinct pain resilience patterns for men and women. The Gender Role Expectations of Pain Questionnaire (GREP) was developed to examine the impact of these beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Women with chronic pain report greater hostility and dismissal 45 and are more likely to have their pain attributed to psychological issues. 46 These disparities appear to be reinforced through gender stereotypes that attribute distinct pain resilience patterns for men and women. The Gender Role Expectations of Pain Questionnaire (GREP) was developed to examine the impact of these beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…These scenarios, and accom-panying graphical prescription opioid histories, are provided in the Supplementary Appendix. We created mock patient interview videos to present the scenarios, each of which featured a white male actor between 28 and 56 years of age, to minimize potential discriminatory prescribing effects-prior research 41,42 has found that opioids are prescribed less frequently for black and female patients.…”
Section: Medication Ordering Entrymentioning
confidence: 99%
“…In humans, females are more likely to endorse rumination (Meints et al, 2017) and rely on social support (Rovner et al, 2017) than males. Perhaps these coping strategies are the result of female patients reporting greater levels of pain dismissal (Igler et al, 2017) and perceived psychologically based pain (Miller et al, 2018) than males. Unfortunately, despite repeated demonstrations that females are more sensitive to painful stimuli (Bartley and Fillingim, 2013), female pain is often discounted at the clinical level.…”
Section: Sex Differences In Psychological Variables Affecting Painmentioning
confidence: 99%